Physicochemical, Technological and Sensory Properties of Chicken Meatballs Processed with Dietary Fibers - KILINCCEKER, O.; TAHSIN YILMAZ, M. (Journal of the Hellenic Veterinary Medical Society, 2019)
In this study, raw chicken meatball samples were incorporated with apple, lemon and pea fibers at different concentrations (0, 4, 8 and 12%). Their physicochemical properties were evaluated at different refrigerated storage time spots (1st, 5th and 10th days) while the fried samples were investigated with respect to their color, technological and sensory properties. The results revealed that the physicochemical properties of raw samples were significantly (P <0.05) affected by fiber type and concentration within the storage periods while color, technological and sensory properties of the fried samples were also significantly changed (P <0.05) according to the fiber type and concentration. Thiobarbutiric acid reactive substance values of raw samples incorporated with the fibers were observed to be lower than those of the control samples at the end of the storage period, indicating that fiber addition could delay lipid oxidation increasing their storage stability. Fiber addition affected the brightness (L* values), redness (a* values) and yellowness (b* values) of both the raw and fried samples. Regarding technological properties of the fried samples, fiber addition generally increased (P <0.05) frying yield, and moisture retention values up to 4%, followed by a decrease at further concentrations. Meatball diameter decreased by addition at level of 4% for all fiber types, but further increase in the fiber concentration did not decrease these values. The maximum fat retention was observed in the fried samples incorporated with the apple and lemon fibers at 12 % concentration. Sensory properties were affected by fiber concentration up to 8%, which constituted the highest tolerated concentration. As a result, fiber addition positively affected the physicochemical and technological properties of the meatballs, but this affect was strongly related to the fiber type and its concentration.